2022
DOI: 10.1002/lary.30505
|View full text |Cite
|
Sign up to set email alerts
|

In reference to Intranasal Corticosteroid Treatment on Recovery of Long‐Term Olfactory Dysfunction Due to COVID‐19

Abstract: This is a commentary on the article by Hosseinpoor et al. Laryngoscope , 2022

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Kasiri et al [ 26 ] and Hintschich et al [ 27 ] treated patients with persistent ODs after SARS-CoV-2 infection with mometasone furoate as in our study without detecting significant benefits. This was confirmed by the recent meta-analysis of Kim et al [ 30 ] and is likely related to poor delivery of the corticosteroid spray to the olfactory epithelium [ 31 , 32 ]. Similarly, oral corticosteroids also did not demonstrate a clear advantage in terms of olfactory recovery compared to olfactory training alone [ 28 ].…”
supporting
confidence: 53%
“…Kasiri et al [ 26 ] and Hintschich et al [ 27 ] treated patients with persistent ODs after SARS-CoV-2 infection with mometasone furoate as in our study without detecting significant benefits. This was confirmed by the recent meta-analysis of Kim et al [ 30 ] and is likely related to poor delivery of the corticosteroid spray to the olfactory epithelium [ 31 , 32 ]. Similarly, oral corticosteroids also did not demonstrate a clear advantage in terms of olfactory recovery compared to olfactory training alone [ 28 ].…”
supporting
confidence: 53%
“…In addressing OD in patients with neocoronary pneumonia, a range of therapeutic approaches have been evaluated, including oral supplementation, topical medications, nasal rinses, and olfactory training. Hosseinpoor et al (2022) and Vaira et al (2022) studied the effect of intranasal corticosteroid treatment on long-term OD recovery caused by COVID-19. At the same time, Veronese et al (2022) found that the combination of olfactory rehabilitation and oral supplementation of palmitoyl ethanolamine and lidocaine can improve the treatment effect of post-conjunctivitis OD.…”
Section: Interventions Of Odmentioning
confidence: 99%